Immune cells and the trajectories of depression, anxiety, and cognitive function among people with amyotrophic lateral sclerosis - Yihan Hu; Elie Deeba; Ulf Kläppe; Linn Öijerstedt; John Andersson; Nicolas Ruffin; Fredrik Piehl; Caroline Ingre; Fang Fang; Christina Seitz (Brain, Behavior, & Immunity - Health)
Background: Amyotrophic lateral sclerosis (ALS) represents a complex syndrome characterized by motor, psychiatric, and cognitive symptoms, where associations between cellular immune features and non-motor manifestations remain unknown. Methods: In this cohort study, we enrolled 250 incident people with ALS (pwALS) assessed with the Hospital Anxiety and Depression Scale, and 226 pwALS with the Montreal Cognitive Assessment, including 218 overlapping pwALS. All individuals were diagnosed between January 2015 and January 2023 in Stockholm, Sweden. We applied joint latent class models to delineate distinct trajectories of anxiety, depression, and cognition, incorporating survival outcomes. A majority of the pwALS had data on leukocyte counts and flow cytometric analyses using a comprehensive T cell panel. We then used immune cell subtypes measured at diagnosis to predict trajectories of these outcomes following ALS diagnosis. Results: We identified two distinct trajectories for anxiety, depression, and cognitive function following ALS diagnosis. PwALS with longer survival displayed more stable trajectories, while those with shorter survival showed decreasing anxiety symptom, increasing depressive symptom, and declining cognitive function. Higher count of leukocytes at the time of ALS diagnosis tended to associate with anxiety and depression trajectories related to shorter survival. Among T cell subpopulations, several CD8+ T cell subsets were associated with a stable trajectory of depressive symptom, and, in turn, better survival. Conclusion: ALS-associated psychiatric and cognitive trajectories vary significantly between pwALS with different prognosis. Certain T cell subsets measured at diagnosis might be indicative of depression trajectories post-diagnosis.